Classical political economy and secular stagnation - Manuel Cruz Luzuriaga; Daniele Tavani (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2021)
This paper presents a model of secular stagnation, income and wealth distribution, and employment in the Classical Political Economy tradition, that can be contrasted with the accounts by Piketty (2014) and Gordon (2015). In these explanations, an exogenous reduction in the growth rate g -because of declining fertility or the exhaustion of path-breaking scientific discoveries-increases the difference with the rate of return to capital r. The capital-income ratio rises, and if the elasticity of substitution is above one, the wage share falls. Both Piketty and Gordon assume full employment at all times. In our explanation, which does not presuppose full employment, the key tension is between profit-driven capital accumulation and wage-driven labor-augmenting technical change: both are defining for Classical Political Economy, and have been emphasized in recent heterodox macro literature. Labor-crushing institutional or technological shocks initially foster capital accumulation -which is profit-driven- and increase wealth inequality. However, the effect on long-run growth is negative, because of the reduced incentives by firms to introduce labor-saving innovation, which is wage-driven. The capital/income ratio must rise in order to restore balanced growth in the long run; and the increase in wealth inequality is permanent. The ultimate effect on long-run employment depends on the strength of the response of labor-augmenting technical change vs. the response of real wage growth to labor market institutions: accordingly, long-run employment can either be wage-led or profit-led. We then test the model using time-series data for the US (1990-2019): the test offers support to the main predictions of our model, and to the employment-population ratio being wage-led.
Keywords: D31; D33; E11; E24; E25; 330; Secular Stagnation; Factor Shares; Wealth Inequality; Employment